Non-directional Photoreceptors in the Pluteus of Strongylocentrotus purpuratus - Valero-Gracia, Alberto; Petrone, Libero; Oliveri, Paola; Nilsson, Dan-Eric; Arnone, Maria I. (Frontiers in Ecology and Evolution, 2016)
In comparison to complex visual systems, non-directional photoreception – the most primitive form of biological photodetection – has been poorly investigated, although it is essential to many biological processes such as circadian and seasonal rhythms. Here we describe the spatiotemporal expression pattern of the major molecular actors mediating light reception – opsins – localized in the Strongylocentrotus purpuratus larva. In contrast to other zooplanktonic larvae, the echinopluteus lacks photoreceptor cells with observable shading pigments involved in directional visual tasks. Nonetheless, the echinopluteus expresses two distinct classes of opsins: a Go-opsin and a rhabdomeric opsin. The Go-opsin, Sp-opsin3.2, is detectable at early (3 days post fertilization) and four armed pluteus stages (4 days post fertilization) in two cells that flank the apical organ. To rule out the presence of shading pigments involved in directional photoreception, we used electron microscopy to explore the expression domain of Go-opsin Sp-opsin3.2 positive cells. The rhabdomeric opsin Sp-Opsin4 expression is detectable in clusters of cells located around the primary podia at the five-fold ectoderm pentagonal disc stage (day 18-21) and thereafter, thus indicating that Sp-Opsin4 may not be involved in the photoreception mechanism of the larva, but only of the juvenile. We discuss the putative function of the relevant cells in their neural context, and propose a model for understanding simple photodetection in marine larvae.